Dopaminergic and noradrenergic integrity are differentially associated with late‐life memory performance. (20th December 2022) - Dahl, Martin J; Bachman, Shelby L; Dutt, Shubir; Düzel, Sandra; Lindenberger, Ulman; Kühn, Simone; Werkle‐Bergner, Markus; Mather, Mara
Abstract: Background: Age‐related deficits in dopaminergic neuromodulation play a key role in determining memory decline. Facilitated by technical advancements, recent research has also implicated noradrenergic neuromodulation in shaping late‐life memory development. However, investigations disentangling the contribution of the two neuromodulators to the neurobiological basis of human cognitive aging are scarce. Method: We collected high‐resolution magnetic resonance imaging (MRI) data of the dopaminergic substantia nigra–ventral tegmental area and the noradrenergic locus coeruleus of 320 younger and older adults at two time points (T1, T2; ∼1.9 years delay). The imaging protocol included three scans sensitive for the substantia nigra–ventral tegmental area and locus coeruleus—a Fast‐Spin‐Echo [FSE] sequence, and a Magnetization‐Transfer sequence, acquired once with a dedicated magnetic saturation pulse [MT+] and once without, resulting in a proton‐density like image [MT–]. We aggregated the information shared across imaging modalities by estimating multimodal latent factors expressing dopaminergic and noradrenergic integrity. Participants also completed a comprehensive cognitive battery at three time points (T1, T2, T3), including tests of fluid intelligence, episodic and working memory. We used structural equation modeling to evaluate cross‐sectional associations of substantia nigra–ventral tegmental area and locus coeruleus integrity with late‐life cognition. In a second set of models, we probed longitudinal changes in substantia nigra–ventral tegmental area and locus coeruleus integrity (T1–T2) and used them to predict participants' future cognitive performance (at T3). Result: Cross‐sectionally, we found differential associations of dopaminergic and noradrenergic nuclei with late‐life cognition. While locus coeruleus integrity was related to better episodic memory across several memory tasks, substantia nigra–ventral tegmental area integrity was related to working memory performance. Moreover, consistent with a largely shared biosynthesis of the neuromodulators, dopaminergic and noradrenergic nuclei were positively related. Longitudinally, we found that older age was associated with more‐negative change in substantia nigra–ventral tegmental area and locus coeruleus integrity (T1–T2). Importantly, changes in locus coeruleus integrity reliably predicted future episodic memory performance (at T3). Conclusion: These findings support the utility of in‐vivo indices for catecholaminergic integrity and highlight differential roles of dopaminergic and noradrenergic neuromodulation in late‐life cognitive decline.